A new study on fractional Schamel Korteweg-De Vries equation and modified Liouville equation - Koc, Dilara Altan; Pandir, Yusuf; Bulut, Hasan (Elsevier, 2024)
Traveling wave solutions of fractional partial differential equations have great importance in the literature. The diversity of solutions plays an important role in understanding the physical structure of the model it represents. For this reason, two important differential equations with the fractional order, which have a significant role in applied sciences and can model real-life problems most accurately, have been solved by the generalized G/G -expansion method in this study. This method is a generalization of the classical G/G -expansion method. With this developed method, the non-linear fractional Schmael Korteweg-De Vries equation and fractional modified Liouville differential equations are discussed to find their exact solutions. In this way, new exact solutions of these equations that were not previously included in the literature have been found. The presented method has been applied to these two equations for the first time, and various new traveling wave solutions have been obtained. Thus, the study goes beyond other studies. To understand the physical behavior of these new exact solutions, three-dimensional graphs have been drawn according to different parameter values.
Keywords: New generalized (G'/G)-expansion method; Schamel Korteweg-De Vries equation; Modified Liouville equation; Analytical solution; Fractional calculus